THE IMPACT OF COVID-19 OUTBREAK ON AIR POLLUTION LEVELS USING ARIMA INTERVENTION MODELLING: A CASE STUDY OF JAKARTA, INDONESIA - Dyah Makutaning Dewi; Ariful Romadhon; Istu Indah Setyaningsih; Ika Yuni Wulansari (Jurnal Meteorologi dan Geofisika, 2022)
Jakarta is a region with a high number of COVID-19 cases in Indonesia. This study investigates the impact of the COVID-19 pandemic and the resulting large scale social restriction on air pollution levels in Jakarta, Indonesia, by studying particulate matter (PM10) levels. This study employs ARIMA intervention using daily COVID-19 case data from January 1, 2020 to September 30, 2020 (the period before and after the first case of COVID-19 in Indonesia on March 2, 2020). The analysis shows COVID-19 started to impact PM10 in Jakarta on the 11th day after confirming the first case in Indonesia, which is indicated by an unordinary increase in PM10 level. However, on the 12th day after intervention, the PM10 level decreases. This occurred at the beginning of the period when large-scale social restrictions are imposed. However, one month after intervention, PM10 increases again and continues to increase until the end of the study. This is allegedly because people are accustomed to being ignorant and bored with the pandemic situation. Social restrictions and movements are no longer effective, which results in the rise of PM10 levels again. Hence, it can be concluded that COVID-19 impacts air quality in Jakarta even though the impact is minimal and in the short term.